The Liver X Receptor Promotes Immune Homeostasis via Controlled Activation of the Innate Immune System in the Liver - Hiroyuki Nakashima; Bradley M. Kearney; Manabu Kinoshita (Biomolecules)
The liver is an indispensable metabolic organ, responsible for accumulating and transporting various nutritional compounds in hepatocytes. However, the transport of these materials from the liver is an energetically intensive task because they contain a considerable number of hydrophobic components, including free cholesterol, and require specialized transfer proteins to shuttle these substances through an aqueous phase. Liver X receptors (LXRs) induce the expression of cholesterol transporters in macrophages to transport free cholesterol derived from apoptotic cells into extracellular space via high-density lipoproteins. Additionally, LXRs control innate immune cells through two major mechanisms: upregulating the phagocytic activity of macrophages and suppressing inflammatory reactions to prevent aggressive activation of immune cells. Therefore, the primary role of LXRs is to accelerate efferocytosis without provoking inflammation and facilitate the transfer of free cholesterol from the intracellular space. This mechanism makes the innate immune system a substantial contributor to systemic metabolic control. Concomitantly, LXRs are important factors in regulating systemic defense mechanisms through the efficient regulation of immune cells. LXR activation, therefore, has great potential for clinical applications in the treatment of metabolic, infectious, and autoimmune diseases. In this review, we discuss the current understanding of the link between LXRs and innate immune cells in the liver, along with prospects for clinical applications of LXR agonists.